Estudio de las características fisicoquímicas de los carbones mesoporosos obtenidos utilizando sílica mesoporosa tipo SBA-16 como molde (2010)
ABSTRACT: The objective of this work is to determine the porous and chemical characteristics of mesoporous carbons synthesized by using SBA-16 mesoporous silica as template. The evaluation of the ability of adsorbing dyes contributes to the physicochemical characterization of these materials. Two SBA-16 mesoporous silica with different porous characteristics are used as templates and sucrose and ethylene are the sucrose sources. The pore size and volume of the mesoporous carbons can be modulated by the selection of the template. It does not occur for the chemical properties.